Multimodal brain image analysis and mathematical foundations of computational anatomy : 4th International Workshop, MBIA 2019, and 7th International Workshop, MFCA 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 17, 2019, Proceedings /: 4th International Workshop, MBIA 2019, and 7th International Workshop, MFCA 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 17, 2019, Proceedings. (2019) - Unknown
No abstract available